Cobalt sulfide nanoparticles: Synthesis, water splitting and supercapacitance studies. (April 2020) - Akram, Rehana; Khan, Malik Dilshad; Zequine, Camila; Zhao, Chen; Gupta, Ram K.; Akhtar, Masood; Akhtar, Javeed; Malik, Mohammad Azad; Revaprasadu, Neerish; Bhatti, Moazzam H.
Abstract: Different alkyl xanthate complexes of cobalt (alkyl = Ethyl, Hexyl, Octyl) were synthesized and used for the synthesis of nanoparticles by a solvent-less route. The p -XRD of the nanoparticles showed the formation of the CoS phase only from all precursors. The effect of size and surface capping on energy generation and energy storage applications was investigated. The electrocatalytic performance of the synthesized samples for hydrogen (HER) and oxygen evolution reaction (OER), indicates that CoS synthesized from the octyl xanthate complex (CoS-Oct) showed higher electrocatalytic performance. A lower over potential of 325 mV and 200 mV was observed for CoS-Oct, at a current density of 10 mA/cm 2, for OER and HER, respectively. The charge storage performance was also investigated, where an inverse trend was observed i.e. the highest specific capacitance (1500 F/g, at scan rate 2 mV/s) was observed for the CoS sample synthesized from ethyl xanthate (CoS-ET). Similarly, the discharge time for CoS-ET was longer as compared to the other samples, suggesting better performance for the charge storage applications. The use of cobalt xanthate complexes for the preparation of CoS by melt method, and the effect of self-capped and uncapped surface of CoS on supercapacitance and OER/HER performance, has never been investigated before.